2015
DOI: 10.4103/0972-0707.148899
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of Root ZX and Raypex 6 in teeth with different apical diameters

Abstract: Background:There is a growing interest about electronic apex locators for working length determination. There are several studies dealing with their performance in different conditions.Aims:The aim of this study is to evaluate the accuracy of Root ZX and Raypex 6 in teeth with different apical diameters.Materials and Methods:Actual working length (AWL) of 80 single rooted teeth were determined as 0.5 mm short of apical foramen. The teeth were divided into 4 groups (n = 20). First group (G 0) included teeth wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 27 publications
4
17
0
4
Order By: Relevance
“…They used a microscope at 20x magnification and a computer based measuring system to evaluate the accuracy of Raypex 5. Aydın et al ( 37 ) evaluated the accuracies of Raypex 6 and Root ZX in teeth having different apical diameters. They reported that accuracy of Raypex 6 decreased with increasing apical diameter and athe ccuracy of Raypex 6 was 85% in mature apex.…”
Section: Discussionmentioning
confidence: 99%
“…They used a microscope at 20x magnification and a computer based measuring system to evaluate the accuracy of Raypex 5. Aydın et al ( 37 ) evaluated the accuracies of Raypex 6 and Root ZX in teeth having different apical diameters. They reported that accuracy of Raypex 6 decreased with increasing apical diameter and athe ccuracy of Raypex 6 was 85% in mature apex.…”
Section: Discussionmentioning
confidence: 99%
“…The reported accuracy rate is 85%-95%, even with electrolytes. [8][9][10][11][12] The 1996 study by Shabahang et al [13] reports a reliability rate of up to 96.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Akisue ve ark., 11 Aydın ve ark. 24 ve Herrera ve ark. 10 taşkın preparasyon yapılmış kök kanallarında elektronik apeks bulucuların doğruluklarını değerlendirdikleri çalışmalarında taşkın preparasyon sırasında da el eğelerini kullanmışlardır.…”
Section: Discussionunclassified
“…10,11,24 Yine aynı araştırmacılar apikal foramen çaplarının 0.32 mm, 0.47 mm ve 0.60 mm'den dar olduğu durumlarda elektronik apeks bulucuların doğruluklarının kabul edilebilir olduğunu göstermişlerdir. 10,11,24 Fouad ve ark. 25 yaptıkları çalışmada apikal foramenin kritik çapının 0.3-0.4 mm olduğunu ve daha geniş apikal foramenlerde hatalı ölçümlerin artacağını bildirmişlerdir.…”
Section: Discussionunclassified